Gender trait preferences among smallholder cowpea farmers in northern Ghana: lessons from a case study - Jinbaani, Alhassan Nuhu; Owusu, Emmanuel Yaw; Mohammed, Abdul-Razak; Tengey, Theophilus Kwabla; Mawunya, Michael; Kusi, Francis; Mohammed, Haruna (Frontiers in Sociology, 2023)
Introduction This case study reports on how a gender responsive breeding program contributes to meeting the trait preference of men and women for improved cowpea varieties in northern Ghana. Methods Fifty-eight early-maturing, medium-maturing and dual-purpose cowpea lines were planted at the CSIR-SARI research fields and women and men farmers invited for participatory plant breeding (PPB) in 2016. Selected lines from the PPB were further evaluated in 2017 using participatory varietal selection (PVS) in 5 districts in northern Ghana. In addition, 20 focus group discussions (FGDs) were held in 2018 in 10 randomly selected communities with 260 participants (130 women and 130 men) across the districts where the PVS had been held previously. Results and discussion The study finds drought tolerance, short cooking time and pest resistance to be the most preferred cowpea traits among both men and women. The study also finds that gender differences exist in trait preference, especially for traits such as seed coat color, earliness, pod above canopy and indeterminate growth habit. As breeding programs focus on improving genetic gains for tolerance of biotic and abiotic stresses, equal attention must be given to breeding for traits desired by women.